Inclusão dos servidores com deficiência da Universidade Federal do Maranhão do campus de São Luís/MA: desafios e possibilidades - LEMOS, Joseana Costa (2021)
The research talks about the theme of the inclusion of disabled servers at the Federal University of Maranhão. For the discussion of the theme, we started from the historical tour on the construction of the rights of people with disabilities who fight for the applicability of the fundamental rights, which make up the human dignity. The legislation that deals with the rights of the people with disabilities is put, but the struggle for its implementation is unceasing, because the society is still cast by barriers in full accessibility and attitudes. In this context, the research problem questions how the process of inclusion of disabled servers has been occurring at the Federal University of Maranhão, Campus São Luís/MA. In order to respond to this problem, the main objective of this study is to analyze how the inclusion process of disabled To achieve the proposed objective, an exploratory, descriptive research with a qualitative approach was carried out. The participants were 33 people, 20 employees with disabilities and 13 managers who work directly with these servers in the institution surveyed. Written official documents, statistical sources and semi-structured interviews were used in the data collection. The results reveal that, although the jobs reservation policy in civil service examination for people with disabilities is applied at UFMA, according to legal determination, there is still a need for a policy of institutional inclusion that glimpses the extinction of the paradigm of integration and outlines measures promoting accessible space for disabled workers to develop their works, activities, with safely , equity and autonomy. It was concluded that despite the guarantee of access of disabled servers to the Institution, it is still necessary actions based on the seven dimensions of accessibility that glimpses the free stay of barriers to employees with disabilities. The improvements pointed out by the participants to the research in relation to the inclusive professional environment will enable the development of affirmative actions that recognize and respect the motto "Nothing about us, without us" as well as respond to the need for a work environment free of architectural and athenatoline barriers to disabled employees of the Federal University of Maranhão.